I believe this is a geometric sequence.
Do you mean a_{n }= (-1)^{n }* (n+1) ?
In that case, just plug in n=15.
a_{15} = (-1)^{15} * (15+1) = -1 * 16 = -16
I believe this is a geometric sequence.
Do you mean a_{n }= (-1)^{n }* (n+1) ?
In that case, just plug in n=15.
a_{15} = (-1)^{15} * (15+1) = -1 * 16 = -16
Comments
Yes, thanks so much!!
What about this one?
find the 3rd term in the sequence: a_{n }=(-1)^{n+1}5^{n+1}
a_{3} = (-1)^{3}^{+1}5^{3+1} = (-1)^{4}5^{4 }= 1*625 = 625
Now see if you can compute some other problems with calculating terms in sequences. These two examples should give you the enough of an idea. I assume these are from a textbook. Good Luck!
Thanks! But would it not be -625?